1977
DOI: 10.1152/ajpheart.1977.232.6.h571
|View full text |Cite
|
Sign up to set email alerts
|

Arteriolar reactive hyperemia: modification by inhibitors of prostaglandin synthesis

Abstract: Several studies implicate endogenously synthesized prostaglandins in the mediation of reactive hyperemic responses in the coronary, renal, and skeletal muscle circulations. We sought additional evidence to involve locally released prostaglandins in the mediation of reactive hyperemia in skeletal muscle at the level of the microcirculation. The cremaster muscle of pentobarbital-anesthetized Wistar-strain rats was prepared for direct in vivo observation and measurement of postocclusive responses of single arteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
16
0

Year Published

1980
1980
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 0 publications
3
16
0
Order By: Relevance
“…A continuous dilating effect of prostaglandins in arteriolar vessels in vivo was also found by other investigators in the skeletal muscle of the rat [14,28]. However, indometha cin did not always reduce resting diameters in this partic ular preparation [29], Nevertheless, some results suggest that prostaglandins can contribute directly or indirectly to the control of basal vascular tone in vivo. Inhibition of prostaglandin synthesis resulted in an elevation of blood pressure in awake dogs [30] and in healthy humans [31],…”
Section: Discussionsupporting
confidence: 74%
“…A continuous dilating effect of prostaglandins in arteriolar vessels in vivo was also found by other investigators in the skeletal muscle of the rat [14,28]. However, indometha cin did not always reduce resting diameters in this partic ular preparation [29], Nevertheless, some results suggest that prostaglandins can contribute directly or indirectly to the control of basal vascular tone in vivo. Inhibition of prostaglandin synthesis resulted in an elevation of blood pressure in awake dogs [30] and in healthy humans [31],…”
Section: Discussionsupporting
confidence: 74%
“…2). Earlier studies in heart and striated muscle preparations have demonstrated heterogeneity in the RH response in microvessels as well as differences between 2A and 3A vessels (2,9,14,22,23,34). The present study demonstrates that differences in shear stress sensitivity underlie branch differences in RH duration, whereas the heterogeneity in recovery times between vessels of the 2A branch are explained by differences in actual shear stress levels at the beginning of RH (Fig.…”
Section: Microvascular Responses During Rhsupporting
confidence: 57%
“…RH responses of second-order (2A) and third-order (3A) vessels were measured in cremaster muscle (15,22,23) of control C57Bl/6 mice and hypercholesterolemic mice. To induce hypercholesterolemia, we placed C57Bl/6 mice and transgenic ApoE3-Leiden mice on a high-fat/high-cholesterol (HFC) diet.…”
mentioning
confidence: 99%
“…In normal subjects, the postocclusive hyperemic response has been shown to be blunted by cyclooxygenase inhibitors, which suggests a role for dilating prostaglandins (12)(13)(14).…”
mentioning
confidence: 99%